Low-frequency stimulation of the primary focus retards positive transfer of secondary focus - Yifang Kuang (Nature Portfolio, 2017)
Abstract Positive transfer of secondary focus (PTS) refers to new epileptogenesis outside the primary focus and is minimally controlled by existing treatments. Low-frequency stimulation (LFS) has benefits on the onset of epilepsy and epileptogenesis. However, it’s unclear whether LFS can retard the PTS in epilepsy. Here we found that PTS at both contralateral amygdala and ipsilateral hippocampus were promoted after the primary focus was fully kindled in rat kindling model. The promotion of PTS at the mirror focus started when the primary kindling acquisition reached focal seizures. LFS retarded the promotion of PTS when it was applied at the primary focus during its kindling acquisition, while it only slightly retarded the promotion of PTS when applied after generalized seizures. Meanwhile, we found the expression of potassium chloride cotransporter 2 (KCC2) decreased during PTS, and LFS reversed this. Further, the decreased expression of KCC2 was verified in patients with PTS. These findings suggest that LFS may be a potential therapeutic approach for PTS in epilepsy.